BEGGING FOR CHANGE: THE ROLE OF SOCIAL WORK IN ADDRESSING THE EXPLOITATION OF CHILD BEGGARS IN INDIAN CITIES - Dr. Bharati Pramod Gaikwad (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Child begging is a visible and distressing social issue in many Indian cities, reflecting deeper systemic problems such as poverty, child trafficking, lack of education, and social neglect. This research paper explores the phenomenon of child begging through the lens of social work, aiming to understand the root causes, the structures that perpetuate exploitation, and the role of social work in intervention and rehabilitation. Relying exclusively on secondary data, the study analyzes reports, surveys, academic studies, and NGO publications to build a comprehensive overview of the issue. Findings indicate that a significant percentage of child beggars are under the control of organized networks or coerced by family members, with poverty being the most cited reason. Demographic analysis from government and NGO reports shows that children aged 11–15 years are most frequently involved in begging, making them highly vulnerable to physical and emotional abuse. Social work agencies have made measurable progress in addressing this issue, especially through education-based interventions, rehabilitation centers, and street outreach programs. However, these efforts face challenges due to inadequate funding, legal loopholes, and public apathy. The study employs a descriptive-analytical methodology and presents data across three thematic tables: demographics of child beggars, primary causes of begging, and the impact of various social work interventions. The discussion highlights the critical need for multi-level interventions, including stricter enforcement of child protection laws, awareness campaigns, and increased collaboration between government bodies and NGOs. In conclusion, the paper argues that social work has a vital role in mitigating the problem of child begging, not just through direct intervention, but also by advocating for policy reform and systemic change. The fight against child begging must be holistic, addressing both individual cases and the broader socio-economic factors that sustain the cycle of exploitation.